Ovarian Epithelial Dysplasia and Prophylactic Oophorectomy for Genetic Risk. Issue 1 (1st January 2009) - Chêne, Gautier; Penault-Llorca, Frederique; Le Bouëdec, Guillaume; Mishellany, Florence; Dauplat, Marie-Melanie; Jaffeux, Patricia; Aublet-Cuvelier, Bruno; Pouly, Jean Luc; Déchelotte, Pierre; Dauplat, Jacques
Abstract : Objective: To make an accurate histopathological description of ovarian dysplasia in a population at genetic risk of ovarian cancer and devise an ovarian dysplasia score. Materials and Methods: In this retrospective cohort study, 90 patients who had undergone bilateral oophorectomy or ovarian cystectomy between 1992 and 2005 and whose ovaries were reported as normal were divided into two groups: Group A comprising prophylactic oophorectomies for genetic predisposition (N = 28), and Group B or control group, fertile and non-cancerous (N = 62). Eleven epithelial cytological and architectural features were defined. Ovaries were analysed and reviewed by four pathologists blinded to clinical data. An ovarian dysplasia score was devised to quantify extent of ovarian epithelial abnormalities. The degrees of ovarian epithelial abnormalities (dysplasia scores) were compared between the two groups. Results: Mean dysplasia score was significantly higher in Group A (prophylactic oophorectomies) than in Group B (control group) (9.67 vs. 4.19, P < 0.001). In Group A, we observed a gradation in the severity of the dysplastic lesions between (i) proven BRCA mutations and prophylactic oophorectomies without mutations (11.26 vs. 8.1), and (ii) according to age (10.27 after age 50 years vs. 8.6 before age 50 years, P = 0.2962). Conclusion: These results suggest abnormalities in ovaries from high risk women. The ovarian dysplasia may be a pre-malignant, non-invasive histological lesion that could be an important step in early neoplasia.